A Common Origin for Guanidinobutanoate Starter Units in Antifungal Natural Products1. Issue 49 (11th November 2013) - Hong, Hui; Fill, Taicia; Leadlay, Peter F.
<x xml:space="preserve">Abstract</x> Keeping it basic: Arginine provides the exotic 4‐guanidinobutanoate starter unit for two different types of zwitterionic polyketide (an example for one type is shown in the picture) produced by the same Streptomyces bacterium. The three‐step precursor pathway is initiated by a remarkable decarboxylating monooxygenase with high specificity for arginine.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>